Fluorescence lifetime-based sensing of polymersome leakage. Issue 2 (12th December 2016) - Wang, Stephan; Chen, Zhong-Ren
Abstract : The time-resolved fluorescence technique enables us to differentiate between polymer degradation and vesicle leakage by employing fluorescence lifetimes and their amplitudes. Abstract : Assays to analyze the degradation, lysis and leakage of vesicles are commonly utilized in biology and physical chemistry. Here we show the fluorescence lifetime-based sensing of the leakage of stimuli responsive PEG114 - b -PLA167 block copolymer vesicles. The time-resolved technique differentiates between the fluorophore molecules in the solvated state at high concentrations, and in the wall material and in the solvated state at low concentrations. The vesicle leakage occurs after an incubation period, which was detected by the change of the time correlated single photon counting decays.